STRATEGI GURU PENDIDIKAN AGAMA ISLAM PADA PENGELOLAAN KELAS DI SMP NEGERI I BANJARBARU - Saifuddin Saifuddin; Dwi Setiawati (STAI AL FALAH Banjarbaru, 2023)
AbstractBased on the data obtained, the implementation of the Islamic Religious Education teacher's strategy in class management at SMP 1 Negeri Banjarbaru has carried out well, the role of the teacher in learning activities is felt to be very crucial because the teacher has a big responsibility in developing student personality, especially what happens in class. Therefore teachers are required to have skills in classroom management, in this case the researcher examines how Islamic Religious Education teachers' strategies are in managing SMP Negeri 1 Banjarbaru.The objectives of this research are: 1. To describe the strategy of PAI teachers to create a conducive teaching and learning atmosphere in the classroom to improve student achievement at SMP Negeri 1 Banjarbaru. 2. To describe the strategy for PAI teachers to establish good cooperative relationships with students in class in improving student learning achievement at SMP Negeri 1 Banjarbaru. 3 to describe the strategy of PAI teachers in managing classroom learning in student achievement at SMP Negeri Banjarbaru. The results of the study showed that the classroom management carried out by the PAI teacher at SMP Negeri 1 Banjarbaru was good. The important thing that must be mastered by the teacher is the strategy in managing the class. The achievement of student learning depends on the actions of the teacher in class.Keywords: Classroom Management, Islamic Religious Education Teacher Strategy. AbstrakBerdasarkan data yang diperoleh pelaksanaan strategi guru Pendidikan Agama Islam pada pengelolaan kelas di SMP 1 Negeri Banjarbaru telah dilakukan dengan baik peran guru dalam kegiatan pembelajaran dirasakan sangat krusial Karena Guru mempunyai tanggung jawab besar dalam perkembangan kepribadian siswa Terutama yang terjadi di kelas. Oleh sebab itu guru dituntut untuk memiliki keterampilan dalam pengelolaan kelas, dalam hal ini peneliti mengkaji Bagaimana strategi guru Pendidikan Agama Islam pada pengelolaan SMP Negeri 1 BanjarbaruAdapun yang menjadi tujuan penelitian ini adalah: 1. Untuk mendeskripsikan strategi guru PAI Menciptakan suasana belajar mengajar yang kondusif Di kelas dalam meningkatkan prestasi belajar siswa di SMP Negeri 1 Banjarbaru. 2. Untuk mendeskripsikan startegi guru PAI menjalin hubungan kerjasama yang baik dengan siswa di kelas dalam meningkatkan prestasi belajar siswa di SMP Negeri 1 Banjarbaru. 3 untuk mendeskripsikan strategi guru PAI mengatur ruang belajar di kelas dalam prestasi belajar siswa di SMP Negeri Banjarbaru. Hasil penelitian menunjukkan bahwa pengelolaan kelas yang dilakukan guru PAI SMP Negeri 1 Banjarbaru ini sudah baik hal penting yang harus dikuasai guru adalah strategi dalam mengelola kelas pencapaian prestasi belajar siswa itu tergantung dari tindakan guru di kelas.Kata kunci: Strategi Guru Pendidikan Agama Islam, Pengelolaan Kelas.